The Effect of Shoulder Flexion Angles on the Recruitment of Upper-extremity Muscles during Isometric Contraction - Moon, Jeheon (The Society of Physical Therapy Science, 2013)
The purpose of this study was to investigate the differences in muscle activation patterns of the biceps brachii (BB) and flexor carpi radialis (FCR) muscles, while measuring the resultant force (RF) at different shoulder flexion angles. [Subjects] Thirteen healthy males (age 24.85±3.4 years, weight; 77.8±7.9 kg; height, 1.7±0.05 m) were enrolled in this study. [Methods] The resultant force was measured by a force transducer . The elbow angle remained constant and the flexion shoulder angle was changed (30°, 45°, 60°, 75° and 90°). [Results] The results of the surface EMG show the largest muscle activities occurred at a shoulder flexion of 75° for BB and 90° for FCR. The largest resultant force was measured at a shoulder flexion angle of 75°. We conclude, that when performing the biceps curl exercise using an arm curl machine, the shoulder should be flexed at 75° to maximize the focus of the exercise for the BB. [Conclusion] These results are useful from the perspective of design as they highlight the differences in the muscle activation of BB and FCR with postural change. Ultimately this knowledge can be used in the design of rehabilitation training for the shoulder as they show that posture can affect muscle activation.